Transmission of muscle force to fascia during exercise. Issue 1 (January 2015) - Findley, Thomas; Chaudhry, Hans; Dhar, Sunil
Summary Objective As the muscle contracts, fibers get thicker, forcing the fascial tubular layers surrounding the muscle (endomysium, perimysium and epimysium) to expand in diameter and hence to shorten in length. We develop a mathematical model to determine the fraction of force generated by extremity muscles during contraction that is transmitted to the surrounding tubes of fascia. Methods Theory of elasticity is used to determine the modulus of elasticity, radial strain and the radial stress transmitted to the fascia. Results Starting with published data on dimensions of muscle and muscle force, we find radial stress is 50% of longitudinal stress in the soleus, medial gastrocnemius, and elbow flexor and extensor muscles. Conclusion Substantial stress is transmitted to fascia during muscular exercise, which has implications for exercise therapies if they are designed for fascial as well as muscular stress. This adds additional perspective to myofascial force transmission research.